Secondary battery
By introducing oxygen atoms with a specific O/S ratio into the positive electrode active material layer of all solid lithium ion batteries, a hydrogen sulfide generation inhibition layer is formed, and the problem of hydrogen sulfide generation during storage and operation of all solid lithium ion batteries is solved, ensuring stable battery performance.
Patent Information
- Application Number
- JP2020193399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-20
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-11-20
AI Technical Summary
The prior art cannot effectively prevent all-solid lithium-ion batteries from producing hydrogen sulfides during storage and normal operation, resulting in degradation of battery performance.
By introducing a specific atomic ratio (O/S ratio ≥3.0) between oxygen atoms and sulfur atoms into the positive electrode active material layer of an all-solid lithium-ion battery, a hydrogen sulfide generation inhibiting layer is formed to prevent the generation of hydrogen sulfide.
It effectively prevents the generation of hydrosulfides during storage and operation of all-solid-state lithium-ion batteries, and maintains the output characteristics and reliability of the batteries.
Smart Images

Figure 0007624303000002 
Figure 0007624303000003 
Figure 0007624303000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary battery. [Background technology]
[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.
[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium-ion secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium-ion secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.
[0004] Currently, lithium-ion secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and for these liquid-based lithium-ion secondary batteries, stricter safety measures against leakage, short circuits, overcharging, etc. are required than for other batteries.
[0005] In recent years, research and development of all-solid-state batteries, such as all-solid-state lithium-ion secondary batteries using oxide- or sulfide-based solid electrolytes, has been actively conducted. A solid electrolyte is a material that is mainly composed of an ion conductor that can conduct ions in a solid state. Therefore, in principle, all-solid-state lithium-ion secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium-ion secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery. All-solid-state lithium-ion secondary batteries using positive electrode active materials made of elemental sulfur (S) or sulfide-based materials, and solid electrolytes containing sulfur, are promising candidates.
[0006] Incidentally, in all-solid-state batteries using materials containing sulfur, the sulfur component may react with moisture to generate hydrogen sulfide (H2S). Hydrogen sulfide has a unique pungent odor, and if it leaks out of the battery's exterior (laminate pack), it may corrode metal parts (connecting members, etc.) in the battery module. Corrosion of metal parts such as connecting members increases contact resistance, resulting in a problem of reduced output characteristics and reliability of the battery module.
[0007] Here, Patent Document 1 discloses a technique for preventing the generation of hydrogen sulfide from a sulfide solid electrolyte when the battery case is broken or the like. Specifically, in the technique described in Patent Document 1, a power generating element is immersed in a flowable sealant (e.g., liquid paraffin) that has properties that do not react with a sulfide-based solid electrolyte film inside a sealed battery case. Then, by disposing a solidification means (a solidification agent such as a metal alkoxide) that solidifies the flowable sealant when the sealed battery case is broken inside the battery case via an isolating member, the solidification agent reacts with the flowable sealant in response to an impact applied to the battery case when the battery case is broken, thereby preventing the generation of hydrogen sulfide from the sulfide solid electrolyte. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-193729 A Summary of the Invention [Problem to be solved by the invention]
[0009] According to the technology described in Patent Document 1, it is possible to prevent to some extent the generation of hydrogen sulfide when the battery case is damaged. On the other hand, the technology described in Patent Document 1 has a problem in that it cannot prevent the generation of hydrogen sulfide when the battery case is not damaged and when the secondary battery is stored after manufacture or during normal operation. Here, it remains preferable to prevent the generation of hydrogen sulfide even when the secondary battery is stored after manufacture or during normal operation.
[0010] Therefore, an object of the present invention is to provide a means for preventing the generation of hydrogen sulfide in a secondary battery using a material containing sulfur, during storage after the battery is manufactured or during steady operation. [Means for solving the problem]
[0011] The present inventors have conducted intensive research to solve the above problems. As a result, they have found that the above problems can be solved by providing a hydrogen sulfide generation suppression region having an atomic ratio (O / S ratio) of oxygen (O) atoms to sulfur (S) atoms of 3.0 or more in at least a part of a solid electrolyte layer containing a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), or in at least a part of a positive electrode active material layer containing a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and have completed the present invention.
[0012] That is, according to one aspect of the present invention, there is provided a secondary battery including a power generating element having a positive electrode including a positive electrode active material layer containing a positive electrode active material, a negative electrode including a negative electrode active material layer containing a negative electrode active material, and a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer and including a solid electrolyte. The secondary battery is characterized in that the solid electrolyte layer contains a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O) and has at least a portion of a hydrogen sulfide generation suppression region in which the atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more, or the positive electrode active material layer contains a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O) and has at least a portion of a hydrogen sulfide generation suppression region in which the atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more. Effect of the Invention
[0013] The hydrogen sulfide generation prevention region in the secondary battery according to the present invention has an atomic ratio of oxygen to sulfur (O / S ratio) of 3.0 or more, and is therefore stable against moisture and has a composition that is less likely to generate hydrogen sulfide. Therefore, the secondary battery according to the present invention prevents the generation of hydrogen sulfide during storage after manufacture of the secondary battery and during steady operation. As a result, the deterioration of the output characteristics and reliability of the secondary battery due to the generation of hydrogen sulfide can also be prevented. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a perspective view showing the appearance of a flat laminated battery which is one embodiment of the all-solid-state battery according to the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of a unit cell layer that constitutes the power generating element of the stacked battery shown in FIGS. [Figure 4]FIG. 4 is an enlarged cross-sectional view of a cell layer 19 constituting a power generating element 21 of a stacked battery 10a according to another embodiment of the present invention. [Diagram 5] FIG. 5 is an enlarged cross-sectional view of a cell layer 19 constituting a power generating element 21 of a stacked battery 10a according to still another embodiment of the present invention. [Figure 6] 2 is a graph showing the results of an analysis of the generation behavior of hydrogen sulfide in Experimental Example 1 described later. [Figure 7] 1 is a graph showing the results of an analysis of the generation behavior of hydrogen sulfide in Experimental Example 3 described below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] One embodiment of the present invention is a secondary battery including a power generating element having a positive electrode including a positive electrode active material layer containing a positive electrode active material, a negative electrode including a negative electrode active material layer containing a negative electrode active material, and a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer and including a solid electrolyte, wherein the solid electrolyte layer includes a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S), and oxygen (O), and has at least a hydrogen sulfide generation suppression region in which the atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more, or the positive electrode active material layer includes a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S), and oxygen (O), and has at least a hydrogen sulfide generation suppression region in which the atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more.
[0016] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation, and may differ from the actual ratios.
[0017] FIG. 1 is a perspective view showing the appearance of a flat laminated type all-solid-state battery which is one embodiment of the secondary battery according to the present invention. FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. 1. The laminated type allows the battery to be compact and have a high capacity. In this specification, the flat laminated type non-bipolar all-solid-state lithium ion secondary battery shown in FIG. 1 and FIG. 2 (hereinafter, also simply referred to as a "laminated type battery") will be described in detail as an example. However, in terms of the internal electrical connection form (electrode structure) of the all-solid-state battery according to this embodiment, it can be applied to both non-bipolar type (internal parallel connection type) batteries and bipolar type (internal series connection type) batteries.
[0018] 1, the stacked battery 10a has a flat rectangular shape, with a negative electrode current collector 25 and a positive electrode current collector 27 for extracting electric power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed with the negative electrode current collector 25 and the positive electrode current collector 27 extending to the outside.
[0019] The all-solid-state battery according to the present embodiment is not limited to a laminated flat shape. A wound all-solid-state battery may be cylindrical, or may be a cylindrical shape modified to have a rectangular flat shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.
[0020] There is also no particular limitation on the removal of the current collectors (25, 27) shown in Fig. 1. The negative current collector 25 and the positive current collector 27 may be pulled out from the same side, or the negative current collector 25 and the positive current collector 27 may each be divided into a plurality of pieces and removed from each side, and are not limited to those shown in Fig. 1 and Fig. 2. In addition, in a wound type lithium ion battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.
[0021] As shown in FIG. 2, the stacked battery 10a of this embodiment has a structure in which a flat, approximately rectangular power generating element 21, in which the charge / discharge reaction actually proceeds, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a structure in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. In this embodiment, the solid electrolyte layer 17 contains an argyrodite-type sulfide solid electrolyte (Li6PS5Cl), which is a type of sulfide solid electrolyte. The negative electrode has a structure in which a negative electrode active material layer 13 containing a negative electrode active material (here, metallic lithium (Li)) is disposed on both sides of a negative electrode current collector 11′. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material (here, elemental sulfur (S)) are disposed on both sides of a positive electrode collector 11". Specifically, the negative electrode, solid electrolyte layer, and positive electrode are laminated in this order, such that one negative electrode active material layer 13 and an adjacent positive electrode active material layer 15 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent negative electrode, solid electrolyte layer, and positive electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 2 has a configuration in which a plurality of unit cell layers 19 are laminated and electrically connected in parallel.
[0022] 2, the outermost negative electrode current collectors located on both outermost layers of the power generating element 21 each have a negative electrode active material layer 13 disposed on only one side, but active material layers may be provided on both sides. In other words, instead of using a current collector exclusively for the outermost layer with an active material layer provided on only one side, a current collector having active material layers on both sides may be used as it is as the outermost layer current collector.
[0023] Negative current collector 11' and positive current collector 11" have a negative current collector (tab) 25 and a positive current collector (tab) 27 attached thereto, which are electrically connected to the respective electrodes (positive and negative electrodes), and are structured so as to be sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Negative current collector 25 and positive current collector 27 may be attached to negative current collector 11' and positive current collector 11" of each electrode by ultrasonic welding, resistance welding, or the like, respectively, via negative electrode leads and positive electrode leads (not shown) as necessary.
[0024] FIG. 3 is an enlarged cross-sectional view of a single cell layer 19 constituting the power generating element 21 of the stacked battery 10a shown in FIGS.
[0025] In this embodiment, as shown in FIG. 2 and FIG. 3, a hydrogen sulfide generation suppression region 18 is provided around the entire periphery of the outer periphery of the solid electrolyte layer 17 (details of the hydrogen sulfide generation suppression region 18 will be described later). Here, the hydrogen sulfide generation suppression region 18 is provided continuously in the lamination direction from the negative electrode active material layer 13 to the positive electrode active material layer 15 at the outer periphery of the solid electrolyte layer 17. As a result, the hydrogen sulfide generation suppression region 18 is adjacent to both the negative electrode active material layer 13 and the positive electrode active material layer 15, and is arranged as a hydrogen sulfide generation suppression layer having a thickness equivalent to that of the solid electrolyte layer 17. In this embodiment, the hydrogen sulfide generation suppression region (hydrogen sulfide generation suppression layer) 18 is provided around the entire periphery of the outer periphery of the solid electrolyte layer 17. As a result, the generation of hydrogen sulfide due to the reaction of the sulfide solid electrolyte with moisture or the like can be effectively prevented around the entire periphery of the outer periphery of the solid electrolyte layer 17.
[0026] In the stacked battery 10a according to this embodiment, the outer peripheral end of the negative electrode active material layer 13 is configured to overlap with the hydrogen sulfide generation suppression region 18 present at the outer peripheral edge of the solid electrolyte layer 17 when the power generating element 21 is viewed in plan. Here, in this specification, an end "overlaps" with a certain region in a plan view means that the end is located between the outer peripheral end and the inner peripheral end of the region in a plan view. Therefore, in the stacked battery 10a according to this embodiment, the outer peripheral end of the negative electrode active material layer 13 is located inside the outer peripheral end of the hydrogen sulfide generation suppression region 18 and outside the inner peripheral end of the hydrogen sulfide generation suppression region 18 when the power generating element 21 is viewed in plan. By positioning the outer peripheral end of the negative electrode active material layer 13 inside the outer peripheral end of the hydrogen sulfide generation suppression region 18, it is possible to effectively prevent the occurrence of a short circuit via the outer peripheral end of the negative electrode active material layer 13 during the manufacture of the battery. On the other hand, by positioning the outer peripheral edge of the negative electrode active material layer 13 outside the inner peripheral edge of the hydrogen sulfide generation suppression region 18, the occurrence of internal short circuits due to dendrite growth during operation of the battery can be effectively prevented.
[0027] In the stacked battery 10a according to this embodiment, the outer peripheral end of the positive electrode active material layer 15 is also configured to overlap with the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge portion of the solid electrolyte layer 17 when the power generating element 21 is viewed in plan. The reaction between the positive and negative electrodes mainly proceeds in the center portion (region other than the hydrogen sulfide generation suppression region 18) of the solid electrolyte layer 17. For this reason, by positioning the outer peripheral end of the positive electrode active material layer 15 outside the inner peripheral end of the hydrogen sulfide generation suppression region 18, it is possible to maximize the effective electrode area and prevent a decrease in battery capacity.
[0028] In addition, in the stacked battery 10a according to this embodiment, the outer circumferential edge of the positive electrode active material layer 15 is configured to be located more inward than the outer circumferential edge of the negative electrode active material layer 13 when the power generating element 21 is viewed in plan. By having the outer circumferential edge of the positive electrode active material layer 15 located more inward than the outer circumferential edge of the negative electrode active material layer 13, the region of the positive electrode active material layer 15 that is less involved in the electrode reaction can be minimized, and a decrease in battery capacity can also be prevented.
[0029] The hydrogen sulfide generation suppression region may be provided continuously in the stacking direction from the negative electrode active material layer 15 to the positive electrode active material layer 13 as shown in FIG. 3, or may be provided only in a portion of the stacking direction.
[0030] 3, when the solid electrolyte layer 17 contains a sulfide solid electrolyte, a hydrogen sulfide generation suppression region 18 is provided in a part of the solid electrolyte layer 17. According to the present invention, there is also provided an embodiment in which the hydrogen sulfide generation suppression region 18 is provided in the positive electrode active material layer 15. Specifically, when the positive electrode active material layer 15 contains a material containing sulfur, the generation of hydrogen sulfide in the positive electrode active material layer 15 can be prevented by providing the hydrogen sulfide generation suppression region 18 in the positive electrode active material layer 15.
[0031] FIG. 4 is an enlarged cross-sectional view of a cell layer 19 constituting a power generating element 21 of a stacked battery 10a according to another embodiment of the present invention.
[0032] In this embodiment, as shown in FIG. 4, a hydrogen sulfide generation suppression region 18 is provided around the entire periphery of the outer periphery of the positive electrode active material layer 15. Here, this hydrogen sulfide generation suppression region 18 is provided continuously in the lamination direction from the solid electrolyte layer 17 to the positive electrode current collector 11″ at the outer periphery of the positive electrode active material layer 15. As a result, the hydrogen sulfide generation suppression region 18 is adjacent to both the solid electrolyte layer 17 and the positive electrode current collector 11″ and is arranged as a hydrogen sulfide generation suppression layer having a thickness equivalent to that of the positive electrode active material layer 15. Also, in this embodiment, the hydrogen sulfide generation suppression region (hydrogen sulfide generation suppression layer) 18 is provided around the entire periphery of the outer periphery of the positive electrode active material layer 15. This makes it possible to effectively prevent hydrogen sulfide generation caused by reaction of elemental sulfur (S) as the positive electrode active material or the sulfide solid electrolyte contained in the positive electrode active material layer 15 with moisture or the like around the entire periphery of the positive electrode active material layer 15.
[0033] The above-mentioned hydrogen sulfide generation suppression region 18 may be provided in both the solid electrolyte layer 17 and the positive electrode active material layer 15. Fig. 5 is an enlarged cross-sectional view of a cell layer 19 constituting a power generating element 21 of a stacked battery 10a according to still another embodiment of the present invention.
[0034] 5, in this embodiment, a hydrogen sulfide generation suppression region 18 is provided around the entire outer periphery of the solid electrolyte layer 17 and the outer periphery of the positive electrode active material layer 15. This makes it possible to effectively prevent the generation of hydrogen sulfide caused by the reaction of the sulfide solid electrolyte contained in each layer and elemental sulfur (S) contained in the positive electrode active material layer 15 with moisture and the like around the entire outer periphery of the solid electrolyte layer 17 and the positive electrode active material layer 15.
[0035] In this embodiment, the inner peripheral end of the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the positive electrode active material layer 15 is configured to overlap with the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the solid electrolyte layer 17 when the power generating element 21 is viewed in plan. That is, the inner peripheral end of the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the positive electrode active material layer 15 is located outside the inner peripheral end of the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the solid electrolyte layer 17 when the power generating element 21 is viewed in plan. The reaction between the positive and negative electrodes mainly proceeds in the center of the solid electrolyte layer 17 (area other than the hydrogen sulfide generation suppression region 18). For this reason, the inner peripheral end of the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the positive electrode active material layer 15 is located outside the inner peripheral end of the hydrogen sulfide generation suppression region 18 present in the outer peripheral edge of the solid electrolyte layer 17, so that the effective electrode area can be maximized and a decrease in battery capacity can be prevented.
[0036] The main components of the secondary battery according to this embodiment will be described below.
[0037] [Current collector] The current collector has a function of mediating the movement of electrons from one surface in contact with the positive electrode active material layer to the other surface in contact with the negative electrode active material layer. There is no particular limitation on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.
[0038] Specifically, the metal may be aluminum, nickel, stainless steel, iron, titanium, copper, etc. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, etc. may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, adhesion of the negative electrode active material by sputtering to the current collector, etc.
[0039] The latter conductive resin may be a resin obtained by adding a conductive filler to a non-conductive polymeric material as required.
[0040] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.
[0041] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally 5 to 80 mass % relative to the total mass of the current collector (100 mass %).
[0042] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.
[0043] [Negative electrode active material layer] The negative electrode active material layer includes a negative electrode active material capable of absorbing and releasing lithium ions. From the viewpoint of being able to achieve a high battery capacity, it is preferable that the negative electrode active material essentially includes metallic lithium (Li) or a lithium-containing alloy. The type of these negative electrode active materials is not particularly limited, but the lithium-containing alloy may be, for example, an alloy of lithium and at least one material that can be alloyed with lithium. Here, examples of the material that can be alloyed with lithium include, for example, Si, Au, In, Ge, Sn, Pb, Al, Zn, H, Ca, Sr, Ba, Ru, Rh, Ir, Pd, Pt, Ag, Cd, Hg, Ga, Tl, C, N, Sb, Bi, O, S, Se, Te, Cl, etc. Among these, from the viewpoint of being able to configure a battery with excellent capacity and energy density, it is preferable that the material that can be alloyed with lithium includes at least one element selected from the group consisting of Si, Au, In, Ge, Sn, Pb, Al, and Zn, and more preferably includes Si, Au, or In. In some cases, two or more kinds of negative electrode active materials may be used in combination. Of course, negative electrode active materials other than those mentioned above may be used. For example, carbon materials such as natural graphite, artificial graphite, mesocarbon microbeads (MCMB), highly oriented graphite (HOPG), hard carbon, and soft carbon, Nb2O5, Li4Ti5O 12 Metal oxides such as may also be used.
[0044] The shape of the negative electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc., but a thin film is preferable. When the negative electrode active material is particulate, its average particle size (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.
[0045] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is, for example, preferably in the range of 40 to 100 mass %, and more preferably in the range of 50 to 100 mass %.
[0046] The negative electrode active material layer may further include a solid electrolyte. When the negative electrode active material layer includes a solid electrolyte, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include a sulfide solid electrolyte and an oxide solid electrolyte, and the sulfide solid electrolyte is preferable.
[0047] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5(LPS), LiI-Li3PS4, and LiI-LiBr-Li3PS. 4、 Li3PS 4、 Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2 S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0048] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of the sulfide solid electrolyte having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS 4、 4. Also, examples of the sulfide solid electrolyte having a Li4P2S7 skeleton include a Li-P-S-based solid electrolyte called LPS (for example, Li7P3S 11 ). Further, as the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing a P element. Furthermore, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I). From the viewpoint of excellent ionic conductivity, in a preferred embodiment, the solid electrolyte is Li2S-P2S5, Li7P3S 11 , Li 3.2 P 0.96 S, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 and a sulfide solid electrolyte selected from the group consisting of Li6PS5X (X is Cl, Br, or I).
[0049] When the sulfide solid electrolyte is of the Li2S-P2S5 type, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in terms of molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.
[0050] The sulfide solid electrolyte may be sulfide glass, crystallized sulfide glass, or a crystalline material obtained by a solid phase method. The sulfide glass may be obtained, for example, by mechanical milling (ball mill, etc.) of the raw material composition. The crystallized sulfide glass may be obtained, for example, by heat treating the sulfide glass at a temperature equal to or higher than the crystallization temperature. The ionic conductivity (e.g., Li ion conductivity) of the sulfide solid electrolyte at room temperature (25° C.) is, for example, 1×10 -5 S / cm or more is preferable, and 1×10 -4 It is more preferable that the ionic conductivity of the solid electrolyte is 1.0 S / cm or more. The ionic conductivity of the solid electrolyte can be measured by an AC impedance method.
[0051] Examples of oxide solid electrolytes include compounds having a NASICON structure. An example of a compound having a NASICON structure is represented by the general formula Li 1+x Al x Ge 2-x Compounds represented by the formula (PO4)3 (0≦x≦2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.
[0052] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.
[0053] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 0 to 60 mass %, and more preferably in the range of 0 to 50 mass %.
[0054] The negative electrode active material layer may further contain at least one of a conventionally known conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.
[0055] The conductive assistant is preferably in the form of particles or fibers. When the conductive assistant is in the form of particles, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, etc.
[0056] When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical properties of the battery. In this specification, the "particle diameter of the conductive assistant" means the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle diameter of the conductive assistant" is calculated as the average value of particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0057] When the negative electrode active material layer contains a conductive assistant, the content of the conductive assistant in the negative electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the negative electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the negative electrode active material layer, which can effectively contribute to improving the battery characteristics.
[0058] On the other hand, the binder is not particularly limited, and conventionally known knowledge can be appropriately referred to.
[0059] The thickness of the negative electrode active material layer varies depending on the configuration of the intended all-solid-state battery, but is preferably within the range of, for example, 0.1 to 1000 μm. Note that, when the battery is produced (fully discharged state), the negative electrode active material layer may not be present. In this case, the negative electrode current collector (for example, the above-mentioned metal foil) is adjacent to the solid electrolyte layer.
[0060] [Cathode active material layer] The positive electrode active material layer includes a positive electrode active material. The type of the positive electrode active material is not particularly limited, but sulfur element (S8) or a reduction product of sulfur containing lithium (any of the compounds Li2S8 to Li2S) is preferably used. Here, for example, sulfur element (S8) has an extremely large theoretical capacity of about 1670 mAh / g, and has the advantages of being low cost and abundant in resources. In this case, when the all-solid-state battery is provided in a charged state, the positive electrode active material includes sulfur element (S8). Also, when the all-solid-state battery is provided in a discharged state, the positive electrode active material includes a reduction product of sulfur containing lithium (any of the compounds Li2S8 to Li2S) as described above.
[0061] The positive electrode active material layer may contain a positive electrode active material other than the above-mentioned elemental sulfur (S8) or a reduction product of sulfur containing lithium (any of the above-mentioned compounds Li2S8 to Li2S). However, the ratio of the elemental sulfur or the reduction product of sulfur containing lithium to the positive electrode active material contained in the positive electrode active material layer is preferably 50 to 100 mass%, more preferably 80 to 100 mass%, further preferably 90 to 100 mass%, even more preferably 95 to 100 mass%, particularly preferably 98 to 100 mass%, and most preferably 100 mass%.
[0062] Examples of positive electrode active materials other than elemental sulfur or reduction products of sulfur containing lithium include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbon sulfide, etc., as typified by the compounds described in International Publication No. 2010 / 044437. In addition, inorganic sulfur compounds such as S-carbon composites, TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, MoS2, and MoS3 can also be used. Furthermore, examples of positive electrode active materials that do not contain sulfur include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, positive electrode active materials other than those mentioned above may also be used.
[0063] The shape of the positive electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the positive electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.
[0064] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 40 to 99 mass %, and more preferably within the range of 50 to 90 mass %, for example.
[0065] The positive electrode active material layer may further contain a solid electrolyte, a conductive assistant, and / or a binder, similar to the negative electrode active material layer.
[0066] [Solid electrolyte layer] The solid electrolyte layer of the all-solid-state battery according to this embodiment contains a solid electrolyte as a main component, and is a layer interposed between the positive electrode active material layer and the negative electrode active material layer. In addition, the solid electrolyte layer of the all-solid-state battery according to this embodiment preferably contains a sulfide solid electrolyte as an essential component from the viewpoint of excellent ion conductivity and durability, and in this case, may contain other solid electrolytes. However, the ratio of the sulfide solid electrolyte to the solid electrolyte contained in the solid electrolyte layer is preferably 50 to 100 mass%, more preferably 80 to 100 mass%, further preferably 90 to 100 mass%, even more preferably 95 to 100 mass%, particularly preferably 98 to 100 mass%, and most preferably 100 mass%. The specific forms of the sulfide solid electrolyte and other solid electrolytes contained in the solid electrolyte layer are the same as those described above, so detailed explanations are omitted here.
[0067] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass %, more preferably in the range of 50 to 100 mass %, and further preferably in the range of 90 to 100 mass %.
[0068] The solid electrolyte layer may further contain a binder in addition to the above-mentioned solid electrolyte. The specific form of the binder that can be contained in the solid electrolyte layer is the same as that described above, and therefore a detailed description thereof will be omitted here.
[0069] The thickness of the solid electrolyte layer varies depending on the intended configuration of the all-solid-state battery, but is preferably within the range of 1 to 1000 μm, and more preferably within the range of 10 to 300 μm, for example.
[0070] [Hydrogen sulfide generation suppression area] As described above, in the secondary battery according to the present embodiment, when the solid electrolyte layer contains a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), a hydrogen sulfide generation suppression region having an atomic ratio (O / S ratio) of oxygen (O) atoms to sulfur (S) atoms of 3.0 or more is provided in at least a part of the solid electrolyte layer. Alternatively, when the positive electrode active material layer contains a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), a hydrogen sulfide generation suppression region having an atomic ratio (O / S ratio) of oxygen (O) atoms to sulfur (S) atoms of 3.0 or more is provided in at least a part of the positive electrode active material layer. In this specification, the types of atoms constituting the solid electrolyte layer and the positive electrode active material layer and their atomic composition ratios are measured by X-ray photoelectron spectroscopy (XPS) as used in the examples described later.
[0071] According to the study by the present inventors, it was found that a sulfide solid electrolyte or a positive electrode material having an O / S ratio of 3.0 or more does not generate much hydrogen sulfide even when it comes into contact with moisture or the like. Although the mechanism is not completely clear, it is speculated that a relatively stable film is formed on the surface of a sulfide solid electrolyte or a positive electrode material having an O / S ratio of 3.0 or more, so that the generation of hydrogen sulfide is prevented even when it comes into contact with moisture. In the present invention, the O / S ratio in the hydrogen sulfide generation suppression region may be 3.0 or more, but from the viewpoint of being able to more effectively suppress the generation of hydrogen sulfide, the O / S ratio is preferably 5.6 or more, more preferably 7.3 or more, and even more preferably 7.7 or more. On the other hand, there is no particular limit to the upper limit of this value, but usually 10.0 or less is sufficient.
[0072] There is no particular limitation on the method of providing the hydrogen sulfide generation suppression region made of the sulfide solid electrolyte or positive electrode material having an O / S ratio of 3.0 or more in at least a part of the solid electrolyte layer or positive electrode active material layer, and conventional technical common sense can be appropriately taken into consideration. One example is a method of subjecting a sulfide solid electrolyte containing Li, P, and S (which actually unavoidably contains oxygen (O)) to a water vapor exposure treatment. According to this method, the O / S ratio value in the sulfide solid electrolyte containing Li, P, and S (and O) can be increased to 3.0 or more. According to the study by the present inventors, it has been found that the O / S ratio of the sulfide solid electrolyte before the water vapor exposure treatment is about 1.4.
[0073] Therefore, according to another aspect of the present invention, a method for producing a secondary battery is also provided, which includes forming the above-mentioned hydrogen sulfide generation suppression region by water vapor exposure treatment. That is, another aspect of the present invention relates to a method for producing a secondary battery, which includes exposing a solid electrolyte layer precursor containing a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), a sulfur-containing positive electrode active material containing sulfur (S), or a positive electrode active material layer precursor containing the sulfide solid electrolyte to water vapor, or exposing a power generating element containing the solid electrolyte layer precursor and the positive electrode active material layer precursor to water vapor, thereby providing a hydrogen sulfide generation suppression region in which the atomic ratio (O / S ratio) of oxygen (O) atoms to sulfur (S) atoms is 3.0 or more in at least a part of the precursor. In this specification, the solid electrolyte layer (raw material) before the hydrogen sulfide generation suppression region is formed by water vapor exposure treatment is referred to as the "solid electrolyte layer precursor". Similarly, the positive electrode active material layer (raw material) before the hydrogen sulfide generation suppression region is formed by water vapor exposure treatment is referred to as the "positive electrode active material layer precursor".
[0074] In the method for producing a secondary battery according to the present embodiment, the specific conditions of the water vapor exposure treatment are not particularly limited. For example, the raw material solid electrolyte layer precursor or the positive electrode active material layer precursor may be left in a water vapor atmosphere, or the raw material solid electrolyte layer precursor or the positive electrode active material layer precursor may be placed in a water vapor flow. If it is desired to form a hydrogen sulfide generation suppression region only in the outer peripheral portion of the solid electrolyte layer precursor or the positive electrode active material layer precursor by such an operation, the above-mentioned water vapor exposure treatment may be performed in a state where a mask is placed on a portion corresponding to the region where the hydrogen sulfide generation suppression region is not desired to be formed (for example, the central region of each layer). In addition, the hydrogen sulfide generation suppression region may be formed collectively on the outer peripheral portion of the solid electrolyte layer precursor and the outer peripheral portion of the positive electrode active material layer precursor by performing the water vapor exposure treatment on the power generation element precursor including the solid electrolyte layer precursor and the positive electrode active material layer precursor.
[0075] The water vapor exposure treatment can be carried out, for example, by flowing the carrier gas, such as helium, through the solid electrolyte layer precursor or the positive electrode active material layer precursor in a state where the dew point of the carrier gas is adjusted, as described in the Examples section below. At this time, there is no particular limitation on the temperature of the solid electrolyte layer precursor or the positive electrode active material layer precursor to be subjected to the water vapor exposure treatment, but it is preferably about 20 to 55°C, more preferably 25 to 50°C. There is also no particular limitation on the dew point of the carrier gas, but it is preferably about -40 to +15°C. Note that the lower the dew point of the carrier gas, the larger the O / S ratio of the solid electrolyte layer or the positive electrode active material layer obtained by the water vapor exposure treatment tends to be. There is also no particular limitation on the time of the water vapor exposure treatment, but it is preferably about 10 to 200 minutes, more preferably 30 to 150 minutes.
[0076] It has been known that hydrogen sulfide is generated when a material containing sulfur comes into contact with moisture, but the phenomenon that the amount of hydrogen sulfide generated decreases over time by actively exposing a sulfur-containing material to water vapor, and finally the generation of hydrogen sulfide is almost nonexistent, was not known. The present invention was completed based on the knowledge of such a new phenomenon discovered by the present inventors. And it was unexpected that a member capable of suppressing the generation of hydrogen sulfide can be obtained by daring to adopt a water vapor exposure treatment that actively brings a sulfur-containing material into contact with moisture, which was previously considered to be avoided. Therefore, it can be said that the present invention, which was completed in a way that overturns such conventional common sense, has patentability over the conventional technology.
[0077] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The negative electrode current collector plate 25 and the positive electrode current collector plate 27 may be made of the same material or different materials.
[0078] [Positive and negative leads] Although not shown in the figures, the current collectors (11', 11") and the current collecting plates (25, 27) may be electrically connected via positive and negative electrode leads. As the constituent materials of the positive and negative electrode leads, materials used in known lithium ion secondary batteries may be similarly used. Note that the parts removed from the exterior are preferably covered with a heat-resistant insulating heat-shrink tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing electric leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).
[0079] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in Figs. 1 and 2, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.
[0080] 1 and 2 has a configuration in which a plurality of unit cell layers are connected in parallel, and thus has a high capacity and excellent cycle durability. Therefore, the stacked battery according to this embodiment is suitable for use as a driving power source for EVs and HEVs.
[0081] Although one embodiment of the all-solid-state battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the description of the claims.
[0082] For example, the type of battery to which the lithium ion secondary battery according to the present invention can be applied includes a bipolar battery including a bipolar electrode having a positive electrode active material layer electrically bonded to one surface of a current collector and a negative electrode active material layer electrically bonded to the opposite surface of the current collector.
[0083] In addition, the secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur.
[0084] The liquid electrolyte (electrolytic solution) that can be used has a form in which a lithium salt is dissolved in an organic solvent. Examples of the organic solvent that can be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl acetate (MA), methyl formate (MF), 4-methyldioxolane (4MeDOL), dioxolane (DOL), 2-methyltetrahydrofuran (2MeTHF), tetrahydrofuran (THF), dimethoxyethane (DME), propylene carbonate (PC), butylene carbonate (BC), dimethyl sulfoxide (DMSO), and γ-butyrolactone (GBL). Among these, from the viewpoint of further improving the rapid charging characteristics and output characteristics, the organic solvent is preferably a chain carbonate, more preferably at least one selected from the group consisting of diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC), and more preferably selected from ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC).
[0085] Examples of the lithium salt include Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), Li(C2F5SO2)2N, LiPF6, LiBF4, LiClO4, LiAsF6, and LiCF3SO3. Among these, the lithium salt is preferably Li(FSO2)2N (LiFSI) from the viewpoints of battery output and charge / discharge cycle characteristics.
[0086] The liquid electrolyte (electrolytic solution) may further contain additives other than the above-mentioned components. Specific examples of such compounds include ethylene carbonate, vinylene carbonate, methylvinylene carbonate, dimethylvinylene carbonate, phenylvinylene carbonate, diphenylvinylene carbonate, ethylvinylene carbonate, diethylvinylene carbonate, vinylethylene carbonate, 1,2-divinylethylene carbonate, 1-methyl-1-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-1-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, and 1-ethyl-2-vinylethylene carbonate. Examples of the additives include ethylene carbonate, vinyl vinylene carbonate, allyl ethylene carbonate, vinyloxymethyl ethylene carbonate, allyloxymethyl ethylene carbonate, acryloxymethyl ethylene carbonate, methacryloxymethyl ethylene carbonate, ethynyl ethylene carbonate, propargyl ethylene carbonate, ethynyloxymethyl ethylene carbonate, propargyl oxyethylene carbonate, methylene ethylene carbonate, and 1,1-dimethyl-2-methylene ethylene carbonate. These additives may be used alone or in combination of two or more. The amount of additive used in the electrolyte solution may be appropriately adjusted.
[0087] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.
[0088] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. A large-capacity, high-output assembled battery suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large-capacity assembled battery, can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.
[0089] [vehicle] The all-solid-state battery according to the present invention maintains its discharge capacity even after long-term use and has good cycle characteristics. Furthermore, it has a high volumetric energy density. In vehicle applications such as electric vehicles, hybrid electric vehicles, fuel cell vehicles, and hybrid fuel cell vehicles, higher capacity, larger size, and longer life are required compared to electric and portable electronic device applications. Therefore, the nonaqueous electrolyte secondary battery can be suitably used as a power source for vehicles, for example, a power source for driving a vehicle or an auxiliary power source.
[0090] Specifically, a battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a long-life battery with excellent long-term reliability and output characteristics can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if a battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as trains, and can also be used as a mounted power source for an uninterruptible power supply device, etc. EXAMPLES
[0091] The present invention will be described in more detail below with reference to examples, although the technical scope of the present invention is not limited to the following examples.
[0092] <Water vapor exposure treatment of sulfide solid electrolyte> <Experimental Example 1> (Preparation of sulfide solid electrolyte) First, an argyrodite-type sulfide solid electrolyte (Li6PS5Cl), which is a type of sulfide solid electrolyte, was prepared as a sample.
[0093] (Water vapor exposure treatment) The solid electrolyte sample prepared above was weighed in a porcelain dish and sealed in a test vessel in the form of a pellet. Note that the atmospheric gas in this experiment was helium (He).
[0094] Next, the test container was placed inside a thermostatic chamber set at 25° C., and it was confirmed that the temperature of the thermostatic chamber was stable. After that, helium (He) gas with a dew point adjusted to 13° C. was circulated inside the test container at a flow rate of 0.2 L / min for 120 minutes, thereby subjecting the solid electrolyte sample to a water vapor exposure treatment.
[0095] (Analysis of the surface composition of solid electrolyte samples using XPS method) The surface composition of the solid electrolyte sample (pellet) that had been subjected to the water vapor exposure treatment as described above was analyzed using X-ray photoelectron spectroscopy (XPS). In addition, the ratio of the amount of oxygen (O) atoms to the amount of sulfur (S) atoms (atomic ratio) was calculated from the obtained analysis results. The results are shown in Table 1 below.
[0096] (Analysis of hydrogen sulfide generation behavior) The gas generated from the solid electrolyte sample by the water vapor exposure treatment was collected in a gas bag. The hydrogen sulfide concentration in the collected gas was measured using a gas detector tube to analyze the behavior of hydrogen sulfide generation from the sample. The gas bag was collected every 10 minutes.
[0097] <Experimental Example 2> Except for setting the temperature of the thermostatic bath to 50° C., the solid electrolyte sample was subjected to a water vapor exposure treatment in the same manner as in the above-mentioned Experimental Example 1, and the surface composition and hydrogen sulfide generation behavior were analyzed. The results are shown in Table 1 below.
[0098] <Experimental Example 3> The dew point of the helium gas circulated inside the test vessel was set to -30°C or lower. Specifically, helium gas was circulated inside the test vessel directly from a helium gas cylinder. Other than this, the solid electrolyte sample was subjected to a water vapor exposure treatment in the same manner as in the above-mentioned Experimental Example 2, and the surface composition and hydrogen sulfide generation behavior were analyzed. The results are shown in Table 1 below.
[0099] <Experimental Example 4> The dew point of the helium gas circulated inside the test vessel was set to -30°C or lower. Specifically, helium gas was circulated inside the test vessel directly from a helium gas cylinder. Except for this, the solid electrolyte sample was subjected to a water vapor exposure treatment by the same method as in the above-mentioned Experimental Example 1, and the surface composition and the generation behavior of hydrogen sulfide were analyzed. The results are shown in Table 1 below. The values of the composition ratio of each element listed in Table 1 are values obtained by rounding the value of the composition ratio of each element (for others, the total value of other elements) calculated to one decimal place to an integer. The values of the O / S ratio listed in Table 1 are values obtained by rounding the value of O / S calculated from the element composition ratio of O and S calculated to one decimal place to two decimal places.
[0100] [Table 1]
[0101] From the results shown in Table 1, it can be seen that by subjecting a sulfide solid electrolyte sample to a water vapor exposure treatment and adjusting the conditions at that time, it is possible to control the increase and decrease of the atomic composition ratio of sulfur (S) atoms and the atomic composition ratio of oxygen (O) atoms in opposite directions. As a result, it can also be seen that the water vapor exposure treatment adopted in Experimental Examples 1 to 4 makes it possible to control the O / S ratio to be 3.0 or more. In addition, when the elemental composition ratio of the surface of a solid electrolyte sample was analyzed by XPS in the same manner without subjecting it to a water vapor exposure treatment and the O / S ratio was calculated to be about 1.4.
[0102] In addition, the results (graphs) of the analysis of the hydrogen sulfide generation behavior in Experimental Example 1 and Experimental Example 3 are shown in FIG. 6 (Experimental Example 1) and FIG. 7 (Experimental Example 3), respectively. The vertical axis of the graphs shown in FIG. 6 and FIG. 7 is the relative value of the amount of hydrogen sulfide generated in each experimental example. As can be seen from these graphs, although hydrogen sulfide is generated as the water vapor exposure treatment progresses, the amount of hydrogen sulfide generated becomes almost zero after a certain time has passed, and hydrogen sulfide is not generated even after contact with water vapor. From this, it can be seen that, according to the secondary battery of the present invention, the presence of the hydrogen sulfide generation suppression region in the solid electrolyte layer and the positive electrode active material layer, which have an O / S ratio value of 3.0 or more, can effectively prevent the generation of hydrogen sulfide during storage after the manufacture of the battery and during the operation of the battery. In addition, from the comparison between FIG. 6 and FIG. 7, it is considered that the larger the O / S ratio value, the stronger the effect of suppressing the generation of hydrogen sulfide. [Explanation of symbols]
[0103] 10a Stacked battery, 11 negative electrode current collector, 12 positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 electrolyte layer, 18 Hydrogen sulfide generation suppression area, 19 cell layer, 21 Power generation elements, 25 negative electrode current collector (negative electrode tab), 27 Positive current collector (positive tab), 29 Laminating film.
Claims
1. a positive electrode including a positive electrode active material layer containing a positive electrode active material; a negative electrode including a negative electrode active material layer containing a negative electrode active material; a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer and including a solid electrolyte; A power generating element having the solid electrolyte layer includes a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and has at least a portion of a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 5.6 or more; or the positive electrode active material layer comprises a sulfur-containing positive electrode active material that contains sulfur (S) and / or a sulfide solid electrolyte that contains lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and at least a portion of the positive electrode active material layer has a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 5.6 or more.
2. a positive electrode including a positive electrode active material layer containing a positive electrode active material; a negative electrode including a negative electrode active material layer containing a negative electrode active material; a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer and including a solid electrolyte; A power generating element having the solid electrolyte layer includes a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and has a hydrogen sulfide generation suppression region in which the atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more in at least a part of an outer periphery of the solid electrolyte layer, but not in a central portion of the solid electrolyte layer; or a positive electrode active material layer including a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and a hydrogen sulfide generation suppression region having an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) of 3.0 or more is provided in at least a part of an outer periphery of the positive electrode active material layer, but not provided in a central portion of the positive electrode active material layer.
3. a positive electrode including a positive electrode active material layer containing a positive electrode active material; a negative electrode including a negative electrode active material layer containing a negative electrode active material; a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer and including a solid electrolyte; A power generating element having the solid electrolyte layer includes a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and has at least a portion of a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more; or the positive electrode active material layer includes a sulfur-containing positive electrode active material containing sulfur (S) and / or a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), and has at least a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more; the solid electrolyte layer includes the sulfide solid electrolyte and has the hydrogen sulfide generation suppression region in at least a portion thereof; the hydrogen sulfide generation suppression region is present in at least a part of an outer peripheral edge portion of the solid electrolyte layer, and at least a part of an outer peripheral edge of the positive electrode active material layer overlaps with the hydrogen sulfide generation suppression region when the power generating element is viewed in plan; and a secondary battery configured such that, when the power generating element is viewed in a plan view, the outer peripheral edge of the positive electrode active material layer, which is arranged so as to overlap with the hydrogen sulfide generation suppression region, is positioned more inward than the outer peripheral edge of the negative electrode active material layer.
4. 3. The secondary battery according to claim 1, wherein the solid electrolyte layer contains the sulfide solid electrolyte and has the hydrogen sulfide generation suppression region in at least a portion thereof.
5. 5. The secondary battery according to claim 4, wherein the hydrogen sulfide generation suppression region is present in at least a part of an outer circumferential edge portion of the solid electrolyte layer, and wherein, when the power generating element is viewed in plan, at least a part of an outer circumferential edge of the negative electrode active material layer is arranged to overlap with the hydrogen sulfide generation suppression region.
6. 6. The secondary battery according to claim 4, wherein the hydrogen sulfide generation suppression region is present in at least a part of an outer circumferential edge of the solid electrolyte layer, and wherein at least a part of an outer circumferential edge of the positive electrode active material layer overlaps with the hydrogen sulfide generation suppression region when the power generating element is viewed in a plan view.
7. 7. The secondary battery according to claim 6, wherein, when the power-generating element is viewed in plan, the outer peripheral edge of the positive electrode active material layer, which is arranged so as to overlap with the hydrogen sulfide generation suppression region, is positioned more inward than the outer peripheral edge of the negative electrode active material layer.
8. 4. The secondary battery according to claim 2, wherein the positive electrode active material layer includes the sulfur-containing positive electrode active material and / or the sulfide solid electrolyte, and at least a portion of the positive electrode active material layer has a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more.
9. 9. The secondary battery according to claim 8, wherein the hydrogen sulfide generation suppression region is present in at least a part of an outer circumferential edge portion of the positive electrode active material layer and at least a part of an outer circumferential edge portion of the solid electrolyte layer, and wherein, when the power-generating element is viewed in a plan view, at least a part of an inner circumferential end of the hydrogen sulfide generation suppression region present in the outer circumferential edge portion of the positive electrode active material layer overlaps with the hydrogen sulfide generation suppression region present in the outer circumferential edge portion of the solid electrolyte layer.
10. 10. The secondary battery according to claim 1, wherein an O / S ratio in the hydrogen sulfide generation suppression region is 7.3 or more.
11. The secondary battery according to any one of claims 1 to 10, which is an all-solid-state lithium ion secondary battery.
12. A method for producing a secondary battery, comprising: exposing a solid electrolyte layer precursor comprising a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), a sulfur-containing positive electrode active material containing sulfur (S), or a positive electrode active material layer precursor comprising the sulfide solid electrolyte to water vapor; or exposing a power-generating element precursor comprising the solid electrolyte layer precursor and the positive electrode active material layer precursor to water vapor, thereby providing a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 5.6 or more in at least a part of the precursor.
13. the method includes exposing a solid electrolyte layer precursor including a sulfide solid electrolyte containing lithium (Li), phosphorus (P), sulfur (S) and oxygen (O), a sulfur-containing positive electrode active material containing sulfur (S), or a positive electrode active material layer precursor including the sulfide solid electrolyte to water vapor, or exposing a power generating element precursor including the solid electrolyte layer precursor and the positive electrode active material layer precursor to water vapor, thereby providing a hydrogen sulfide generation suppression region in which an atomic ratio of oxygen (O) atoms to sulfur (S) atoms (O / S ratio) is 3.0 or more in at least a part of the precursor, In this method, the hydrogen sulfide generation suppression region is provided on at least a part of an outer periphery of the precursor, and is not provided in a central portion of the precursor.
Citation Information
Patent Citations
Solid-state battery
JP2009193729A
Sulfide solid electrolyte particle
JP2012094445A
Sulfide solid electrolytic material, positive electrode material, and battery
JP2018026321A
Sulfide solid electrolyte particle and all-solid battery
JP2020115425A